Opportunities and Challenges of Implementing Kinetic Façade Typology in Indonesia - Stephanus Wirawan Dharmatanna; Rani Y Wulandari; Ismail Salam (Indonesian Journal of Energy, 2024)
The application of kinetic facade technology is gaining popularity worldwide as an innovative solution to enhance the environmental quality of buildings. However, in Indonesia, the implementation of kinetic facades remains limited and requires further in-depth study. Thus, our research aims to fill this gap by exploring the opportunities and challenges of implementing kinetic facade typologies in Indonesia. The research method involves a literature review and descriptive analysis. We collect data on the use of kinetic facades globally, analyze the factors influencing their implementation, and identify the opportunities and challenges encountered. The analysis results are expected to provide a better understanding of the implementation of kinetic facades in Indonesia. The identified opportunities include the potential to improve energy efficiency, reduce carbon emissions, and enhance the interior and exterior environmental quality of buildings. The challenges identified may encompass technical aspects, regulations, financial issues, as well as market awareness and acceptance of this new technology. Our study contributes a foundation for further development of kinetic facades in Indonesia. With a better understanding of the opportunities and challenges, architecture practitioners, engineers, and policymakers can take appropriate steps to address the challenges and capitalize on the opportunities to integrate kinetic facades into building designs in Indonesia, promoting sustainable and innovative development in the architecture sector.